Tahap penguasaan Bahasa Melayu pelajar Cina di sebuah sekolah menengah persendirian Cina Klang / Nur Fatin Zulkifli - Nur Fatin , Zulkifli (2017)
The objective of this study is to identify the level of Malay Language through the analysis of Malay language errors in their essay among chinese students in a Chinese Private Secondary School in Klang, categorizing the types of Malay language errors in their essay made by Chinese students in a secondary school (private) and identify the correlation between teaching techniques as a second language. This study uses an error analysis approach in essay writing done by Chinese students. The sample of this study is 30 chinese students as respondents from Junior 3 who speak in their native language as their mother longue. A few methods were used for this study by the researcher such as observation, interview and questionnaire. The theory used in the analysis of error analysis is the Language Acquisition Theory by Corder (1973) which uses the concept of error analysis. Theory of Monitors by Krashen (1981) was also applied in the study of language proficiency and these two theories resulted in a new concept in this language study of Chinese students learning the second language of Malay. The problem faced by the researcher is mechanical errors, morphological errors and syntactic errors. The results showed the highest morphological error followed by mechanical error and syntactic error. A questionnaire involving 100 teachers in Chinese Private Secondary School Kwang Hua was used to identify the correlation between teaching techniques among Chinese students.The researchers use SPPS (Statistical Package for the Social Sciences) version 20. The findings show that all variables are significantly and the results show that teaching techniques are very important in teaching and learning in the classroom.